Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; Philip Barnes; Gary Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2017)
Soybean yields measured from 2014 through 2016 were more than 50% greater from the residual from N-based turkey litter applications during 2011 through 2013 than in the control where no nitrogen (N) or phosphorus (P) was applied. However, residual from P-based turkey litter applications or fertilizer-only did not result in soybean yield different from the no N-P control. This residual effect on yield was largely due to increased pods per plant.
Keywords: soybean; turkey litter; fertilizer; residual; tillage